2014
DOI: 10.1371/journal.pone.0106439
|View full text |Cite
|
Sign up to set email alerts
|

The Association of CHA2DS2-VASc Score and Blood Biomarkers with Ischemic Stroke Outcomes: The Belgrade Stroke Study

Abstract: BackgroundMany blood biomarkers have a positive association with stroke outcome, but adding blood biomarkers to the National Institutes of Health Stroke Scale (NIHSS) did not significantly improve its discriminatory ability. We investigated the association of the CHA2DS2-VASc score with unfavourable functional outcome (defined as a 30-day modified Rankin Scale [mRS] ≥3) in patients presenting with acute ischemic stroke (AIS), and examined whether the addition of blood biomarkers (troponin I [TnI], fibrinogen, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…30) However, this association between hsCRP and ischemic stroke found in univariate analysis in AF patients was lost after multivariate adjustment using the logistic regression model in our study. A similar finding was reported by Potpara, et al 31) where the CHA2DS2-VASc score reliably predicts a short-term, 30-day unfavorable outcome of acute ischemic stroke regardless of the presence or absence of AF, and that adding high-sensitivity TnI or fibrinogen or CRP, or all three biomarkers, to the CHA2DS2-VASc score does not further improve the prediction. Study limitations: First, the small number of patients included in this study is a major limitation.…”
Section: Discussionsupporting
confidence: 87%
“…30) However, this association between hsCRP and ischemic stroke found in univariate analysis in AF patients was lost after multivariate adjustment using the logistic regression model in our study. A similar finding was reported by Potpara, et al 31) where the CHA2DS2-VASc score reliably predicts a short-term, 30-day unfavorable outcome of acute ischemic stroke regardless of the presence or absence of AF, and that adding high-sensitivity TnI or fibrinogen or CRP, or all three biomarkers, to the CHA2DS2-VASc score does not further improve the prediction. Study limitations: First, the small number of patients included in this study is a major limitation.…”
Section: Discussionsupporting
confidence: 87%
“…In stroke patients with nonvalvular AF, both higher CHADS 2 and CHA 2 DS 2 ‐VASc scores predicted a worse clinical outcome . But other studies of stroke patients reported only CHA 2 DS 2 ‐VASc score could predict an unfavourable 30‐day outcome and was useful for stratifying the risk of poor outcome at 3 months following stroke . Although studies have been carried out to investigate the possibility of expanding the use of the CHADS 2 and CHA 2 DS 2 ‐VASc scores from the original purpose of assessing risk of stroke in patients with AF to predict clinical outcomes of patients with acute ischaemic stroke, data from these studies were limited because the follow‐up periods were relatively short and no imaging evidence of infarction severity was reported …”
Section: Introductionmentioning
confidence: 99%
“…
CHA 2 DS 2 -VASc score alone has been reported to predict 30-day risk of stroke reliably [1]. A CHA 2 DS 2 -VASc score of 0 could relatively precisely prompt truly low incidence of stroke, with an annual ischemic stroke rate of approximately 1% [2].
…”
mentioning
confidence: 99%